2022
DOI: 10.1007/s41109-022-00448-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the persistence and consistency of social signatures

Abstract: Human social networks are composed of multiple dynamic and overlapping communication networks, in which membership changes over time. However, less well understood are whether and how our communication patterns are similar or different over time and across various modes of communication. Here, we use data on the frequency of phone calls, text messages, and in-person interactions to examine the social signatures of more than 700 students in a university setting. Our analysis shows that although there is substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Studies of human communication via mobile phones have shown that in line with the above picture, there is a consistent, general pattern in egocentric networks where a small number of close alters receive a disproportionately large share of communication. Data on the frequency of mobile phone calls and text messages also indicate that within this general pattern, there are clear and persistent individual differences 18 22 : some people repeatedly focus most of their attention on a few close relationships, while others tend to distribute communication among their alters more evenly 18 . These differences are stable in time even under high personal network turnover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of human communication via mobile phones have shown that in line with the above picture, there is a consistent, general pattern in egocentric networks where a small number of close alters receive a disproportionately large share of communication. Data on the frequency of mobile phone calls and text messages also indicate that within this general pattern, there are clear and persistent individual differences 18 22 : some people repeatedly focus most of their attention on a few close relationships, while others tend to distribute communication among their alters more evenly 18 . These differences are stable in time even under high personal network turnover.…”
Section: Introductionmentioning
confidence: 99%
“…These differences are stable in time even under high personal network turnover. However, the mechanisms that generate such heterogeneity of tie strengths, its individual-level variation, and the generality of this pattern beyond mobile-phone-mediated communication, have not yet been established 14 , 22 24 .…”
Section: Introductionmentioning
confidence: 99%